A COMPARISON OF 2 DIFFERENT RAPID PALATAL EXPANSION TECHNIQUES FROM THE POINT OF ROOT RESORPTION - (:unkn) unknown (MOSBY-YEAR BOOK INC, 1994)
The aim of this investigation is to compare Haas and Cast Cap Splint devices from the point of root resorption. The material comprised thirty-eight upper and twelve lower premolar teeth derived from nineteen patients who required RME and subsequent removal of the first premolars as part of their full banded orthodontic treatment. Root resorption and repair areas were observed on the buccal surfaces of premolars. Repair tissue was cellular cementum in both groups. There was no significant difference between these two techniques from the point of root resorption amount.